Deep-time Arctic climate archives: high-resolution coring of Svalbard's sedimentary record – SVALCLIME, a workshop report - Senger, Kim; Kulhanek, Denise Kay; Jones, Morgan T.; Smyrak-Sikora, Aleksandra; Planke, Sverre; Zuchuat, Valentin; Foster, William J.; Grundvåg, Sten-Andreas; Lorenz, Henning; Ruhl, Micha; Sliwinska, Kasia K.; Vickers, Madeleine L.; et al. (Scientific Drilling, 2023)
We held the MagellanPlus workshop SVALCLIME “Deep-time Arctic climate archives: high-resolution coring of Svalbard's sedimentary record”, from 18 to 21 October 2022 in Longyearbyen, to discuss scientific drilling of the unique high-resolution climate archives of Neoproterozoic to Paleogene age present in the sedimentary record of Svalbard. Svalbard is globally unique in that it facilitates scientific coring across multiple stratigraphic intervals within a relatively small area. The polar location of Svalbard for some of the Mesozoic and the entire Cenozoic makes sites in Svalbard highly complementary to the more easily accessible mid-latitude sites, allowing for investigation of the polar amplification effect over geological time. The workshop focused on how understanding the geological history of Svalbard can improve our ability to predict future environmental changes, especially at higher latitudes. This topic is highly relevant for the ICDP 2020–2030 Science Plan Theme 4 “Environmental Change” and Theme 1 “Geodynamic Processes”. We concluded that systematic coring of selected Paleozoic, Mesozoic, and Paleogene age sediments in the Arctic should provide important new constraints on deep-time climate change events and the evolution of Earth's hydrosphere–atmosphere–biosphere system.